The crystal structure of 2,2-bis(3-methoxyphenyl)-1-tosyl-1,2-dihydro- 2λ4,3λ4 -[1,3,2]diazaborolo[4,5,1-ij]quinoline - dichloromethane (1/1) - Ding Siyi (Zeitschrift für Kristallographie - New Crystal Structures)
C31H29N2BO4Cl2, triclinic, P1‾ $P\overline{1}$ (no. 1), a = 8.7365(3) Å, b = 11.9533(4) Å, c = 14.3566(5) Å, α = 85.7280(10)°, β = 74.8450(10)°, γ = 85.1990(10)°, V = 1439.88(9) Å3, Z = 2, Rgt (F) = 0.0478, wRref (F 2) = 0.1176, T = 298 K.